Rekonstruksi Pemikiran Sastera Islam Melalui Gagasan Persuratan Baru Janaan Mohd Affandi Hassan - Mohd Adi Amzar Muhammad Nawawi; Muhammad Hakim Kamal; Amirah Ahmad Zain; Khairul Asyraf Mohd Nathir (Nun Gemilang Ent, 2026)
Tier 3- Indexed by MyCite